Development of a Mobile-Based Personal Health Record for Mothers and Children Using Glide App: A Usability Study - Ombong, Deva Indri Saputri; Santoso, Dian Budi (Procedia of Engineering and Life Science, 2024)
The increasing need for efficient personal health records (PHRs) for mothers and children has driven the development of innovative healthcare solutions. This study presents the development and evaluation of "SIKIA," a PHR application created using the Glide App. SIKIA aims to streamline health data management and enhance accessibility for mothers and children.The research methodology involved developing the SIKIA app, followed by user trials and an evaluation using the System Usability Scale (SUS). A group of mothers with young children, pregnant woman, and midwifes participated in the study, testing the application and providing feedback on its usability and functionality.The results indicate that SIKIA is well-received by users. The SUS scores demonstrate high user satisfaction, with users praising the app's ease of use, accessibility, and comprehensive health data management capabilities. The positive feedback highlights SIKIA's potential as a valuable tool in personal health record management, addressing the specific needs of mothers and children. This study underscores the importance of user-friendly PHRs in improving health outcomes and healthcare service efficiency. By providing a seamless platform for health data management, SIKIA can contribute significantly to the well-being of mothers and children. The findings suggest that further development and broader implementation of SIKIA could enhance healthcare delivery and patient engagement in personal health management.